Effectiveness of flow obstructions in enhancing electro-osmotic flow - Perumal Nithiarasu (Microfluidics and Nanofluidics, 2017)
In this paper the influence of obstructions on micro-channel electroosmotic flow is investigated for the first time. To carry out such a study, regular obstructions are introduced into micro-channels and flow rates are numerically calculated. The effect of channel width on flow rates is analysed on both free and obstructed channels. The solid material considered for channel walls and obstructions is silicon and the electrolyte is de-ionised water. The parameters studied include channel width, obstruction size and effective porosity of the channel. The effective porosity is varied between 0.4 and 0.8 depending on other chosen parameters. The results clearly demonstrate that, under the analysed conditions, introduction of obstructions into channels wider than100 micro meters enhances the flow rate induced by electro-osmosis.